2009
DOI: 10.1161/circulationaha.109.849117
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Statin Therapy According to Plasma High-Sensitivity C-Reactive Protein Concentration in the Controlled Rosuvastatin Multinational Trial in Heart Failure (CORONA)

Abstract: Background-We examined whether the antiinflammatory action of statins may be of benefit in heart failure, a state characterized by inflammation in which low cholesterol is associated with worse outcomes. Methods and Results-We compared 10 mg rosuvastatin daily with placebo in patients with ischemic systolic heart failure according to baseline high sensitivity-C reactive protein (hs-CRP) Ͻ2.0 mg/L (placebo, nϭ779; rosuvastatin, nϭ777) or Ն2.0 mg/L (placebo, nϭ1694; rosuvastatin, nϭ1711). The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 27 publications
3
89
1
2
Order By: Relevance
“…It appears that Pravastatin, in addition to having a beneficial effect on the lipid profile, reduces CRP in these patients and has its greatest benefit in patients with the highest CRP levels. These results may imply that inflammation and total cholesterol levels are equally important in atherogenesis 14,24,[26][27][28] . New guidelines from the American Heart Association and the Centers for Disease Control and Prevention (2003) advised doctors to consider testing Americans at moderate risk of heart disease for signs of inflammation in the bloodstream 29) .…”
Section: Discussionmentioning
confidence: 99%
“…It appears that Pravastatin, in addition to having a beneficial effect on the lipid profile, reduces CRP in these patients and has its greatest benefit in patients with the highest CRP levels. These results may imply that inflammation and total cholesterol levels are equally important in atherogenesis 14,24,[26][27][28] . New guidelines from the American Heart Association and the Centers for Disease Control and Prevention (2003) advised doctors to consider testing Americans at moderate risk of heart disease for signs of inflammation in the bloodstream 29) .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic heart failure, the statins can improve endothelial function by inducing constitutive nitric oxide synthase (cNOS) gene transcription (von Haehling et al, 2003) and reduce CRP levels (Kjekshus et al, 2007). McMurray et al (2009) showed in the CORONA study that treatment with rosuvastatin led to better outcome in a subgroup of patients with elevated CRP. Clinical benefits of statin therapy have also been found in patients with chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, 10 mg rosuvastatin daily, in patients with ischemic systolic heart failure, reduced cardiovascular death, myocardial infarction, and stroke mainly in patients with high sensitivity-C reactive protein ≥ 2.0 mg/L. 33 However, further studies are required to recommend routine use of statins in HF after MI. 30 Implantable Cardioverter Defibrillators: Patients with left ventricular dysfunction after myocardial infarction have an increased risk of sudden death due to lethal arrhythmias.…”
mentioning
confidence: 99%